A randomized trial of a multimodal lifestyle intervention in cancer survivors - Brown, Justin C.; Nauta, Phillip; Whitehead, Darryl; Dubin, Benjamin R.; Nash, Ryan; Blumberg, Kate; Green, Tamara; Brown, John; Compton, Stephanie L. E.; Miletello, Gerald P. (Frontiers in Oncology, 2025)
IntroductionCancer survivors are often insufficiently physically active, have overweight or obesity, and suboptimal cardiorespiratory fitness. The Small Steps study evaluated a multimodal intervention to address these modifiable risk factors.MethodsThe study randomized 33 cancer survivors to a 10-week multimodal lifestyle intervention (MLI) of exercise training and nutritional counseling or waitlist control (WLC). The co-primary endpoints included body weight and cardiorespiratory fitness capacity; secondary and exploratory endpoints included cardiometabolic and patient-reported measures. Endpoints were analyzed using analysis of covariance.ResultsParticipants had a mean (SD) age of 60.3 (14.0) years, 26 (79%) were White, and 18 (55%) were survivors of breast cancer. At baseline, the mean body weight was 94.9 (18.3) kg, and the submaximal cardiopulmonary fitness was 16.4 (5.0) mL/kg/min. As compared with WLC, MLI reduced body weight [−2.3 kg (95% CI: −3.6, −0.9); P = 0.0013; −2.8% (95% CI: −4.3, −1.3)] and increased cardiopulmonary fitness [2.0 mL/kg/min (95% CI: 0.3, 3.8); P = 0.022]. MLI reduced waist circumference [−2.9 cm (95% CI: −5.5, −0.3); P = 0.029], fat mass [−1.7 kg (95% CI: −2.9, −0.5); P = 0.005], visceral adipose tissue [−168.0 cm3 (95% CI: −380.4, −27.7); P = 0.019], and improved self-reported vitality [12.2 points (95% CI: 1.6, 22.8); P = 0.024] and social functioning [14.2 points (95% CI: 1.1, 27.4); P = 0.034]. MLI did not reduce lean mass [−0.2 kg (95% CI: −0.8, 0.4); P = 0.52] or bone mineral density [0.004 g/cm3 (95% CI: −0.012, 0.020); P = 0.63]. There were no serious adverse events.DiscussionThe Small Steps program reduced body weight and improved cardiopulmonary fitness in survivors of various types of cancer. This program may contribute to improved health span after cancer.Clinical trial registrationclinicaltrials.gov, identifier NCT04987359.